Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Can anybody help me understand this proof?

In Rotman's 'An introduction to homological algebra' in Proposition 6.75 (iii). Flabby sheaves $\mathcal{L}$ are acyclic (Page 381), in the proof it says

Let $\mathcal{L}$ be flabby. Since there are enough injectives, there is an exact sequence $0 \rightarrow \mathcal{L} \rightarrow \mathcal{E} \rightarrow \mathcal{Q} \rightarrow 0$ with $\mathcal{E}$ injective. Now $\mathcal{E}$ is flabby, by Corollary 6.74 (Corollary 6.74 says that every injective sheaf $\mathcal{E}$ over a space $X$ is flabby), and so $\mathcal{Q}$ is flabby, by part (ii) (Part (ii) says: Let $0 \rightarrow \mathcal{L}' \rightarrow \mathcal{L} \rightarrow \mathcal{Q} \rightarrow 0$ be an exact sequence of sheaves. If $\mathcal{L}'$ and $\mathcal{L}$ are flabby, then $\mathcal{Q}$ is flabby). We prove that $H^{q}(\mathcal{L}) = 0$ by induction on $q \geq 1$. If $q = 1$, the long exact cohomology sequence contains the fragment

$H^{0}(\mathcal{E}) \rightarrow H^{0}(\mathcal{Q}) \rightarrow H^{1}(\mathcal{L}) \rightarrow H^{1}(\mathcal{E})$.

Since $H^{1}(\mathcal{E}) = \left\{ 0\right\}$, we have $H^{1}(\mathcal{L}) = coker(\Gamma(\mathcal{E}) \rightarrow \Gamma(\mathcal{Q}))$. But this cokernel is $0$, by part (i), and so $H^{1}(\mathcal{L}) = \left\{ 0\right\}$...

Q: I don't get where the coker part came from? Why is $H^{1}(\mathcal{L}) = coker(\Gamma(\mathcal{E}) \rightarrow \Gamma(\mathcal{Q}))$?? I'm lost here

share|cite|improve this question
Unrelated: Did "coker" come from here? – user21436 Feb 17 '12 at 16:55
@Kannappan; No. It just means cokernel. – Zhen Lin Feb 17 '12 at 17:28
Unrelateder: ...or from this ? – Georges Elencwajg Feb 17 '12 at 18:14
Haha @GeorgesElencwajg Good one, that's a lovely dog, Swag – Mario Carrasco Feb 20 '12 at 2:00
up vote 4 down vote accepted

The exact sequence fragment $$H^{0}(\mathcal{E}) \rightarrow H^{0}(\mathcal{Q}) \rightarrow H^{1}(\mathcal{L}) \rightarrow H^{1}(\mathcal{E})$$ becomes, after the observation that the last term is $0$, $$H^{0}(\mathcal{E}) \rightarrow H^{0}(\mathcal{Q}) \rightarrow H^{1}(\mathcal{L}) \rightarrow 0.$$ Because this is exact, the map $H^0(\mathcal{Q})\to H^1(\mathcal{L})$ is onto. Therefore, by the isomorphism theorems, $$H^1(\mathcal{L}) \cong \frac{H^0(\mathcal{Q})}{\mathrm{ker}(H^0(\mathcal{Q})\to H^1(\mathcal{L}))}.$$ But since the sequence is exact, $\mathrm{ker}(H^0(\mathcal{Q})\to H^1(\mathcal{L})) = \mathrm{Im}(H^0(\mathcal{E})\to H^0(\mathcal{Q}))$. So: $$H^1(\mathcal{L}) \cong \frac{H^0(\mathcal{Q})}{\mathrm{ker}(H^0(\mathcal{Q})\to H^1(\mathcal{L}))} = \frac{H^0(\mathcal{Q})}{\mathrm{Im}(H^0(\mathcal{E})\to H^0(\mathcal{Q}))} = \mathrm{Coker}(H^0(\mathcal{E})\to H^0(\mathcal{Q})).$$

share|cite|improve this answer
This is awesome, thanks bro – Mario Carrasco Feb 20 '12 at 1:57

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.